PENGATURAN DAN PENGAWASAN BISNIS FINANCIAL TECHNOLOGY DI INDONESIA: Indonesia - Kornelius Benuf; Rinitami Njatrijani; Ery Agus Priyono; Nur Adhim (Dialogia Iuridica, 2020)
In the era of globalization like today, the ease and speed of getting things are highly sought after, including the ease and speed of getting financial services. Financial Technology (Fintech) is a digital financial service that offers and provides convenience and speed of financial services. The emergence of Fintech certainly provides convenience for people to get financial services. But we need to remember that in our constitution, Indonesia is a rule of law so that everything that is done in this country must be based on law. Including the Fintech business, must be regulated and monitored by existing laws in Indonesia. So it is necessary to know the regulation and supervision of Fintech's business in Indonesia, which will be further explained in this paper. The writing method used is normative juridical, using secondary data by analyzing primary, secondary and tertiary legal materials. Based on the research results it is known that Fintech's business in Indonesia is regulated and supervised by three institutions namely the Ministry of Communication and Information, Bank Indonesia, and the Financial Services Authority.